The Efficiency of Local and International Banks in Indonesia - Aba, Fransiskus X Lara Aba; Junior, Antuh (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study uses two stages, first measure the technical effectiveness of banking using the data envelopment analysis (DEA), and the second stage to estimate the influence of macroeconomic variables, namely interest rate, inflation rate, and exchange rate against the efficiency of local and international banks using Tobit's regression model. Based on the results of the measurement of the effectiveness of local and international banks using the DEA method, it was found that on average the level of efficiency of local and international banks have not yet reached the level of effectiveness of optimal 100% and the level of ability of local banks has the higher efficiency level than foreign banks.